2020
DOI: 10.1073/pnas.2014454117
|View full text |Cite
|
Sign up to set email alerts
|

Bitter gourd from Africa expanded to Southeast Asia and was domesticated there: A new insight from parallel studies

Abstract: Matsumura et al. (1) report a chromosome-level genome assembly of Momordica charantia, an important vegetable and medicinal plant in the family Cucurbitaceae, and then use resequencing to infer the divergence between wild samples with "[var.] muricata-type morphology" and cultivated samples (var. charantia). The initial domestication was dated to 6,000 y ago, followed by the separation of further cultivars 800 y ago. A parallel study by Cui et al. (2) (with partly overlapping authorship) instead inferred that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In contrast, Matsumura et al [9] reported that the signals of selection between wild and Southeast Asia (SEA) types predominantly arose from the selection during the SA-SEA divergence stage rather than the result of a gradual and accumulative evolution from wild to SA to SEA. Renner [11], integrating insights from two parallel studies, proposed that the bitter gourd expanded from Africa to Southeast Asia and underwent domestication there [6,11]. The domestication selection of bitter gourd pericarp color is associated with consumer preferences; individuals in the SEA region tend to favor a lighter green pericarp color [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Matsumura et al [9] reported that the signals of selection between wild and Southeast Asia (SEA) types predominantly arose from the selection during the SA-SEA divergence stage rather than the result of a gradual and accumulative evolution from wild to SA to SEA. Renner [11], integrating insights from two parallel studies, proposed that the bitter gourd expanded from Africa to Southeast Asia and underwent domestication there [6,11]. The domestication selection of bitter gourd pericarp color is associated with consumer preferences; individuals in the SEA region tend to favor a lighter green pericarp color [18].…”
Section: Discussionmentioning
confidence: 99%
“…charantia split roughly 1.9 million years ago, while the separation between muricata and charantia happened once again about 6000 years ago. Based on these parallel studies, Renner [11] raised a new insight that bitter gourd from Africa expanded to Southeast Asia and was domesticated there.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Matsumura et al (2020) reported that the signals of selection between wild and Southeast Asia (SEA) types predominantly arose from the selection during the SA-SEA divergence stage, rather than the result of a gradual and accumulative evolution from wild to SA to SEA. Renner (2020), integrating insights from two parallel studies, proposed that the bitter gourd expanded from Africa to Southeast Asia underwent domestication there (Chomicki et al 2020;Renner 2020). The domestication selection of bitter gourd pericarp color is associated with consumer preferences, individuals in the SEA region tend to favor a lighter green pericarp color (Dhillon et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…charantia split roughly 1.9 million years ago, while the separation between muricata and charantia happened once again about 6,000 years ago. Based on these parallel studies, Renner (2020) raised a new insight that bitter gourd from Africa expanded to Southeast Asia and was domesticated there (Chomicki et al 2020;Renner 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although it varies regionally, it usually blooms in June-July and bears fruit in September-November. In Southeast Asia, its fruits are used in salads [15]. It is used to flavor many food products in China.…”
Section: Momordica Charantiamentioning
confidence: 99%